Optic Neuropathy Due to Microbead-Induced Elevated Intraocular Pressure in the Mouse - Chen, Huihui (Association for Research in Vision and Ophthalmology, Inc., 2011)
PURPOSE. To characterize a glaucoma model of mice, the authors adopted and modified a method of inducing the chronic elevation of intraocular pressure (IOP) by anterior chamber injection of polystyrene microbeads. METHODS. Chronic elevation of IOP was induced unilaterally in adult C57BL/6J mice by injecting polystyrene microbeads to the anterior chamber. Effectiveness of microbeads of different sizes (small, 10 μm; large, 15 μm) on inducing IOP elevation was compared, and IOP was measured every other day using a tonometer. After maintaining elevated IOP for 2, 4, or 8 weeks, the degree of RGC and axon degeneration was assessed quantitatively using electron microscopy, fluorogold, retrograde labeling, and immunohistochemistry. RESULTS. Eighty-one of 87 mice that received anterior chamber injection of microbeads exhibited consistent IOP elevation above that of control eyes. Injection of small microbeads induced longer and higher peak value of IOP elevation compared with that of the large microbeads. A single injection of small microbeads resulted in a 4-week elevation of IOP that was maintained to an 8-week period after a second injection of microbeads in week 4. As the duration of IOP elevation increased, RGC bodies and their axons degenerated progressively and reached an approximately 50% loss after an 8-week elevation of IOP. CONCLUSIONS. Anterior chamber injection of microbeads effectively induced IOP elevation and glaucomatous optic neuropathy in mice. Development of an inducible mouse model of elevated IOP will allow applications of mouse genetic technology to the investigation of the mechanisms and the evaluation of treatment strategies of glaucoma.